Penyelidikan Kegagalan pada Alat Pemisah Karet Alam Jenis LRH 410 - Derlini Derlini; Achmad Jusuf Zulfikar (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2022)
This study is an investigation into the causes of failure in a part of a natural rubber separator with water known as a Centrifuge type LRH 410. The part that is damaged is the lock ring which functions as the main lock. The purpose of this study was to obtain a comparison of the values of tensile strength, material hardness, and the composition of the constituent elements of the two types of locks. This investigation includes a field visit to the incident location to collect initial failure data and send samples to the laboratory. Specimens are divided into 2 types, namely damaged lock ring material (LR-R) and good lock ring material (LR-B). Tensile testing was carried out using the standard E8M-99 ASTM metric system. The hardness test uses the Brinell hardness test method. Observation of the microstructure of the lock ring (specimen) aims to determine the microstructure of the specimen. Analysis of the composition of the elements of the lock ring material using a spectrometer. The results of the tensile test showed that the yield strength of the LR-R material was only 50% compared to LR-B. Based on the material hardness test, it can be seen that the LR-R hardness value is lower than LR-B. Based on the results of the composition test, it was found that the content of the element Carbon in LR-R was 50% lower than that of LR-B. Thus the LR-R material will wear out faster when operated compared to the LR-B material.